PERAN MODERASI MOTIVASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK GENERASI Z - Krisnawati Tarigan; Marselia Angelia (Universitas Kristen Krida Wacana, 2025)
This research aims to analyze the influence of tax knowledge, tax socialization, tax awareness, and tax digitalization, as well as to examine the moderating role of tax motivation on the impact of these independent variables on tax compliance among generation Z. This research employing a quantitative method approach utilizes primary data collected through questionnaires. The data sample obtained was 211 respondents who are taxpayers from generation Z and domiciled in DKI Jakarta. Data analysis in this research involved validity test, reliability test, classical assumption testing, and hypothesis testing processed using IBM SPSS software version 25. The findings indicate that tax socialization has a negative influence on tax compliance among generation Z. Tax knowledge, tax awareness, and tax digitalization does not effect on tax compliance among generation Z. Tax motivation is able to moderate the relationship between tax socialization and tax compliance among generation Z. Tax motivation does not moderate the relationship between tax knowledge, tax awareness, and tax digitalization with the tax compliance of generation Z. Keywords: Tax Compliance, Taxpayers, Generation Z, Tax Motivation